Tumeur fibreuse solitaire parautérine: à propos d’un cas - Slimani, Olfa (Pan Afr Med J, 2016)
Solitary fibrous tumors of the female genital tract are extremely rare. We report the case of a 78-year old patient presenting with a pelvic mass. Surgical exploration showed parauterine tumor. Anatomo-pathological examination confirmed the diagnosis of malignant solitary fibrous tumor. The evolution was marked by the death of the patient. It is important to be able to detect these tumors whose evolution can be poor. Long-term follow-up of patients with resectable tumor should be recommended.